Ready-to-use violence prevention skills lessons and activities for secondary students - Begun, Ruth Weltmann; Huml, Frank J. (West Nyack, N.Y. : Center for Applied Research in Education, 1998)
Life skills: making proper decisions; learning to be tolerant; responding to failure; learning to cope with life's problems by using social skills. Respect: developing self-respect; dealing with disrespect. Relationships: developing communication skills; establishing a good relationship; resolving conflicts peacefully... Anger. Family. Stress and danger. Suicide. Stimulants. Crime.
Keywords: Education; School violence; School violence -- United States -- Prevention -- Handbooks, manuals, etc; Conflict management -- United States -- Handbooks, manuals, etc; High school students -- United States -- Handbooks, manuals, etc